Constitutional law interpretation as an integral legal doctrine - A. V. Skorobogatov (Russian Journal of Economics and Law, 2014)
Objective: to view the constitutional law interpretation as an integral legal doctrine, based on the synthesis of natural-legal, normative and juridical-sociological aspects of the Russian Constitution. Methods: dialectic approach to cognition of social phenomena and post-modernist paradigm, which determined the choice of the specific research methods: comparative, hermeneutic, discursive. Results: The article is devoted to the research of “constitutional law interpretation” notion. Basing on the author’s typology of law interpretation, the integral character of the constitutional law interpretation is proved, which determines the essence of the legal reality in Russia. The constitutional law interpretation realizes the synthesis of normative, sociological and natural-legal theory with the leading role of normativism. Scientific novelty: The article for the first time analyzes the essence and content of constitutional law interpretation as an integral legal doctrine. Practical value: The main provisions and conclusions of the article can be used in scientific and educational activity when viewing the issues of the essence and content of law interpretation.